Perioperative Immunosuppression and Risk of Cancer Progression: The Impact of Opioids on Pain Management - Renata Zajączkowska; Wojciech Leppert; Joanna Mika; Magdalena Kocot-Kępska; Jarosław Woroń; Anna Wrzosek; Jerzy Wordliczek (Pain Research and Management)
Opioids comprise an important group of drugs used in cancer pain pharmacotherapy. In recent years, more and more studies have emerged indicating the potentially immunosuppressive effects of opioid analgesics and their serious consequences, including the risk of cancer progression. The identification of these risks has prompted a search for other effective, and most importantly, safer methods of perioperative analgesic management. Regional analgesia techniques, which allow for a significant reduction in opioid dosing and thus diminish the risk of immunosuppression associated with these drugs, seem to offer substantial hope in this respect. A number of studies available in the literature assess the effects of regional analgesia techniques on cancer progression; however, it is often difficult to interpret their results owing to several perioperative factors (such as surgical trauma, inadequate pain and stress relief, and hypothermia) which are also attributed immunosuppressive effects and tend to be implicated in increased risk of cancer progression. Further research is needed to verify the available data on both the potential adverse effects of opioids and the possible protective effects of regional analgesia techniques on cancer patients.